Current Trends and Research Challenges Regarding “Preparation for Oxidative Stress” - Moreira, Daniel C.; Oliveira, Marcus F.; Liz-Guimarães, Lara; Diniz-Rojas, Nilda; Campos, Élida G.; Hermes-Lima, Marcelo (Frontiers in Physiology, 2017)
Survival under stress, such as exposure to hypoxia, anoxia, freezing, dehydration, air exposure of water breathing organisms and estivation, is commonly associated to enhanced endogenous antioxidants, a phenomenon coined ‘preparation for oxidative stress’ (POS). The regulation of free radical metabolism seems to be crucial under these selective pressures, since this response is widespread among animals. A hypothesis of how POS works at the molecular level was recently proposed and relies on two main processes: increased reactive species production under hypoxia, and activation of redox-sensitive transcription factors and signaling pathways, increasing the expression of antioxidants. The present paper brings together the current knowledge on POS and considers its future directions. Data indicate the presence of POS in 83 animal species (71.6% among investigated species), distributed in eight animal phyla. Three main research challenges on POS are presented: i) to identify the molecular mechanism(s) that mediate/induce POS, ii) to identify the evolutionary origins of POS in animals, and iii) to determine the presence of POS in natural environments. We firstly discuss the need of evidence for increased RS production in hypoxic conditions that underlie the POS response. Secondly, we discuss the phylogenetic origins of POS back 700 million years, by identifying POS-positive responses in cnidarians. Finally, we present the first reports of the POS adaptation strategy in the wild. The investigation of these research trends and challenges may prove useful to understand the evolution of animal redox adaptations and how they adapt to increasing stressful environments on Earth.